Kemuhammadiyahan dan Pemberdayaan Perempuan: Menjalin Tradisi dan Modernitas - Gebby Amara Putri; Ajeng Ayundining Utami; Yashinta Khairani; Anisah Azzahra Lubis; Wismanto Wismanto; Wira Ramashar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Muhammadiyah as one of the largest Islamic movements in Indonesia has an important role in empowering women, especially through education and programs that support economic independence. This empowerment aims to increase the role of women in the social and economic development of society. This study aims to analyze Muhammadiyah's efforts in empowering women through various programs, such as education, skills training, and advocacy, and to spread the impact of these programs on women and society as a whole. The study uses a qualitative approach with literature studies and interviews. Relevant literature sources are described, while interviews are conducted with figures in Muhammadiyah and Aisyiyah who are involved in women's empowerment. Muhammadiyah, through the Aisyiyah organization, plays an important role in improving women's welfare through education and skills. Despite facing challenges such as social stigma and violence against women, collaboration with other institutions and the use of information technology show significant potential in increasing women's participation and independence.